(untitled) (Archive of Conferences, 2021)
This article provides information about the life and work of Zahiriddin Muhammad Babur, his military campaigns in his time, his political skills in public administration, and the construction process in Movorounnahr. The article also discusses the scientific heritage of Zahiddin Muhammad Babur and the study of Babur’s works